A Hetero‐Bifunctional Spacer for the Smart Engineering of Carbon‐Based Nanostructures. Issue 4 (21st January 2015) - Tuci, Giulia; Luconi, Lapo; Rossin, Andrea; Baldini, Francesco; Cicchi, Stefano; Tombelli, Sara; Trono, Cosimo; Giannetti, Ambra; Manet, Ilse; Fedeli, Stefano; Brandi, Alberto; Giambastiani, Giuliano
Abstract Efforts have been made in recent years to develop novel functionalisation protocols aimed at imparting multimodality and improved properties to complex carbon‐based nanostructures. The incorporation of cleavable bonds to the nanomaterial surface for the controlled release (or exchange) of specific molecules under appropriate chemical and biological settings is relatively unexplored. The design and synthesis of a hetero‐bifunctional linker joining a "cleavable" disulfide moiety for the covalent anchoring of a wide range of thiol end‐capped (bio)molecules and a "clickable" terminal acetylene group is described. The strategy is based on the well‐established copper‐mediated acetylene–azide coupling reaction between the acetylene linker and single‐walled carbon nanotubes decorated with phenylazido pendant arms. As a result, easily "post‐derivatisable" and traceable nanostructured platforms containing a linking group potentially available for a wide range of biological probes are prepared and completely characterised.